Surface decorated quantum dots: Synthesis, properties and role in herbal therapy - Baig, Mirza Shahed; Suryawanshi, Ravikiran Maheshrao; Zehravi, Mehrukh; Mahajan, Hitendra S.; Rana, Ritesh; Banu, Ahemadi; Subramanian, Muthukumar; Kaundal, Amit Kumar; Puri, Sachin; Siddiqui, Falak A.; Sharma, Rohit; Khan, Sharuk L.; et al. (Frontiers in Cell and Developmental Biology, 2023)
Quantum dots are the serendipitous outcome of materials research. It is the tiny carbonaceous nanoparticles with diameters ranging from 1 to 10 nm. This review is a brief discussion of the synthesis, properties, and biomedical applicability of quantum dots, especially in herbal therapy. As quantum dots are highly polar, they can be surface decorated with several kinds of polar functionalities, such as polymeric molecules, small functional molecules, and so on. The review also consists of the basic physical and optical properties of quantum dots and their excitation―dependent properties in the application section. We focus on therapeutics, where quantum dots are used as drugs or imaging probes. Nanoprobes for several diagnostics are quite new in the biomedical research domain. Quantum dot―based nanoprobes are in high demand due to their excellent fluorescence, non-bleaching nature, biocompatibility, anchoring feasibility for several analytes, and fast point―of―care sensibility. Lastly, we also included a discussion on quantum dot―based drug delivery as phytomedicine.